An improved synthesis of 4-cyano-1,10-phenanthroline, 4,7-dicyano-1,10- phenanthroline and their bis(4,4′-di-tert-butyl-2,2′-bipyridine) ruthenium(II) complexes - Staehle, Robert; Menzel, Roberto; Peuntinger, Katrin; Pilz, T. David; Heinemann, Frank Wilhelm; Guldi, Dirk Michael; Beckert, Rainer; Rau, Sven (Polyhedron, 2014)
This report describes a new palladium catalyzed synthesis of 4-cyano-1,10-phenanthroline (nphen, 1), 4,7-dicyano-1,10-phenanthroline (dnphen, 2) and their corresponding ruthenium complexes. The two cationic complexes, [(tbbpy)Ru(nphen)] 3 and [(tbbpy)Ru(dnphen) ] 4 (tbbpy = 4,4′-di-tert-butyl-2,2′-bipyridine), were synthesized using an improved microwave procedure. All compounds were fully characterized, including the solid-state molecular structures of the complexes. The influence of 1 and 2 on the metal-to-ligand charge transfer (MLCT) transitions were studied and compared to the ruthenium(II) polypyridyl complexes containing the related 4,4′-dicyano-2,2′-bipyridine (dnbpy) and the non-functionalized 1,10-phenanthroline (phen) ligand. © 2014 Elsevier Ltd. All rights reserved.

Carbene based photochemical molecular assemblies for solar driven hydrogen generation. - Peuntinger, Katrin; Pilz, T. David; Staehle, Robert; Schaub, Markus; Kaufhold, Simon; Petermann, Lydia; Wunderlin, Markus; Goerls, Helmar; Heinemann, Frank Wilhelm; Li, Jing; Drewello, Thomas; Vos, Johannes G.; et al. (Dalton Transactions, 2014)
Novel photocatalysts based on ruthenium complexes with NHC (N-heterocyclic carbene)-type bridging ligands have been prepared and structurally and photophysically characterised. The identity of the NHC-unit of the bridging ligand was established unambiguously by means of X-ray structural analysis of a heterodinuclear ruthenium-silver complex. The photophysical data indicate ultrafast intersystem crossing into an emissive and a non-emissive triplet excited state after excitation of the ruthenium centre. Exceptionally high luminescence quantum yields of up to 39% and long lifetimes of up to 2 μs are some of the triplet excited state characteristics. Preliminary studies into the visible light driven photocatalytic hydrogen formation show no induction phase and constant turnover frequencies that are independent on the concentration of the photocatalyst. In conclusion this supports the notion of a stable assembly under photocatalytic conditions.